Regional Economic Outlook, October 2020, Sub-Saharan Africa : A Difficult Road to Recovery. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
Sub-Saharan Africa is struggling to navigate an unprecedented health and economic crisis-one that, in just a few months, has jeopardized decades of hard-won development gains and upended the lives and livelihoods of millions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet